PENGARUH KUALITAS PELAYANAN DAN KERELASIAN NASABAH TERHADAP CITRA PT. BANK NEGARA INDONESIA KOTA JAMBI - Hapzi Ali (Jurnal Ilmiah Universitas Batanghari Jambi, 2009)
Today, banks are facing tight competition. All banks put customer’s satisfaction as their priority of service. PT. BNI 46 of Jambi city is no exception. It is found out that there is a tendicy for BNI 46 Jambi to decrease its market share. This indicates that this bank among customers has relatively bad image. As a result, customers are reluctant to reccomend this bank to their friends. It is believe that the bad images is caused by the fact that BNI 46 Jambi is reluctant ti build good relation with customer. This research find out out that the good relation and services quality simultans taneously affect the images of BNI 46 of Jambi city. Partially, good relation dominantly affect the images and service quality does not have any affect.